Relatório de Estágio Profissional "A Jornada Constrói-se Caminhando: A História de um Estudante Estagiário". - Bruno Filipe Dutra Bacalhau (2017)
This document materializes the narrative of a pre-service teacher about the practicum training, whose dream has always "to be a Teacher". The story tries to expose the feelings and emerged experiences of the pre-service teacher, during the practicum year, as well as the remained "marks". This narrative intends to be the portrait of the path travelled, from the first to last step, a travel that had a school in Porto as stage, which hosted a practicum group, composed of three pre-service teachers and two "architects" - cooperating teacher and faculty supervisor. With regard to the structure, this history is made up of seven major chapters: 1) "Quem sois e onde ides?" - portrays a journey of sharing, learning, difficulties and the many possible paths to follow to be a teacher; 2) "Contextos - as pontes para o entendimento" - report the contexts of pedagogical practice, as well as the understanding of what it is to be a Physical Education Teacher; 3) "O espaço da realidade e dos sonhos" - notice the space where everything happens, as well as its stakeholders; 4) "Do pensamento à realização" - where thought and practice come together; 5) "Espaços de interação" - announce the importance of the relationship and differentiated work, as well curricular project using student-cantered teaching models and reflections about the evaluation process; 6) "Professor fora do pavilhão" - report the work beyond the classroom; and 7) "O final - o que ficou?" - revealed the end of the journey, the learning and farewells that, in reality, are not.